Sprawozdanie z 19th Annual Conference of the European Society of Criminology ConverGHENT Convergent roads, bridges and new pathways in criminology [Zbieżne drogi, mosty i nowe ścieżki w kryminologii] Gandawa (Belgia), 18-21 września 2019 roku - Pawełek, Katarzyna; Rajewska de Mezer, Joanna (Studia Edukacyjne, 2019)
.